Factor analysis and correlation between CIWA-Ar protocol and biochemical-hematic profile in patients with alcohol withdrawal syndrome - L. Carcaño-Calderón; C.O. Ramos-Peñafiel; M. Salcedo-Roldán; I. Díaz-Estrada; F. Galván-Flores; R. Duran-Guzmán; F. Sandoval-Gutiérrez; C. Mendoza-García; A. Santoyo-Sánchez; C. Martínez-Murillo; J. Collazo-Jaloma (Revista Médica del Hospital General de México, 2015)
Background: CIWA-Ar score is the gold standard for stratifying severity of alcohol withdrawal syndrome (AWS). Aim: To identify the correlation between the different scales used in patients with AWS, and with the biochemical–haematological profile. Material and methods: Prospective, analytical observational study in 49 patients with AWS diagnosed between February 2011 and July 2012. Maddrey, Glasgow, MELD, CIWA-Ar scores and laboratory values were obtained at diagnosis. Results: There was no correlation between CIWA-Ar and other scales (R2 = 0.001, p = 0.823, 95%CI); however, a linear relationship (p = 0.000, 95%CI) was found. On the correlation matrix, CIWA-Ar was not associated with any of the study parameters. There were no significant differences in length of stay when analyzed by type of treatment. Conclusion: CIWA-Ar is a good predictor of severity, albeit with no biochemical or hematic correlation.